Pelatihan Etika Bisnis dan Penyusunan Pembukuan Sederhana bagi UMKM Kecamatan Tambaksari Kota Surabaya - Mia Ika Rahmawati; Lilis Ardini; Marsudi Lestariningsih; Wiwiek Srikandi Shabrie (UNIB Press, 2023)
The STIESIA Surabaya community service team provided business ethics and simple bookkeeping records to 15 Tambaksari Village, Surabaya City SMEs owners. The main reason for conducting community service is because the identification of problem that previously done shows that SMEs owners have difficulty in compiling simple bookkeeping for their business. This activity was carried out with four sessions: delivery of business ethics material, presentation of simple bookkeeping material, simple bookkeeping training, and discussion sessions. The result of community service is the increased awareness of SMEs owners of the importance of simple bookkeeping discipline for the sustainability of SMEs businesses.